Safety and immunogenicity of a recombinant M2e–flagellin influenza vaccine (STF2.4xM2e) in healthy adults - Turley, Christine B.; Rupp, Richard E.; Johnson, Casey; Taylor, David N.; Wolfson, Julie; Tussey, Lynda; Kavita, Uma; Stanberry, Lawrence; Shaw, Alan (Vaccine, 2011)
The ectodomain of matrix protein 2 (M2e) is a promising candidate for a broadly protective influenza A vaccine because it is highly conserved and antibodies to M2e are protective in animal models. STF2.4xM2e (VAX102) is a recombinant fusion protein that links four tandem copies of the M2e antigen to Salmonella typhimurium flagellin, a TLR5 ligand used as an adjuvant. The objectives of this first-in-human study were to assess the safety and immunogenicity of VAX102 given as a prime-boost regimen to healthy adults. Sixty subjects 18–49 years old were enrolled in a multicenter, double-blind, randomized, placebo-controlled trial (Study 1). Based on pre-clincial data, initial design included doses starting at 10μg, with an escalation plan. After reactogenicity was noted at the 10μg dose, the trial was redesigned to evaluate 0.3, 1.0, and 3μg doses. Following this study, 16 subjects were enrolled in Study 2, an open label, low dose study, to evaluate doses of 0.03 and 0.1μg. In both trials, vaccine or placebo was given intramuscularly (i.m.) at 0 and 28 days. Clinical and laboratory safety assessments took place 1 and 7 days after immunization. Immune responses to M2e and flagellin were assessed by ELISA at 7, 14 and 28 days after each dose. Seroconversion was defined as a serum IgG anti-M2e antibody value ≥0.174μg/ml and a fourfold rise in concentration. Doses of 0.03–1μg were safe and well tolerated in all subjects. Doses of 0.03 and 0.1μg produced limited immunogenicity (38% and 75% respectively), after the second dose of vaccine. Doses of 0.3 and 1.0μg were immunogenic in 18 (75%) of 24 vaccinees after the first dose and 23 (96%) after the second dose. In the 1.0μg group, the geometric mean M2e antibody concentration was 0.4μg/ml after the first dose and 1.7μg/ml after the booster dose. M2e antibody concentrations and seroconversion rates were not significantly different at higher doses (p>0.05). Immune response to flagellin was robust but did not appear to interfere with M2e antibody responses after the booster dose. Following the first injection of VAX102 at higher doses (3 and 10μg), self-limited but severe symptoms were noted in some subjects and were associated with elevated levels of C-reactive protein. Although not directly measured, this reaction was believed to be mediated by cytokine release. VAX102 was safe and induced high antibody levels to M2e at 0.3 and 1.0μg doses. The TLR5 ligand, S. typhimurium flagellin, is a novel approach to adjuvant-like activity through activation of innate immunity, and when fused to multiple copies of the M2e protein, the vaccine was able to induce a fourfold rise in antibody in humans, to a previously non-immunogenic, highly-conserved portion of the influenza virus. Clinical correlates of protection that may be afforded by M2e antibody in humans are a future focus of investigation.